Border Effect Between Hong Kong and Mainland China. (February 2016) - Fan, Simon C.; Wei, Xiangdong; Wu, Jia
Abstract: This study applies newly developed methodologies to investigate the border effect between Hong Kong and mainland China. It makes three contributions to a better understanding of the border effect puzzle. First, the special relationship between mainland China and Hong Kong provides us with a unique opportunity to disentangle the factors underlying the observed border effect. Second, in addition to estimating the border effect between mainland China and Hong Kong, we also estimate that between the mainland provinces of Guangdong and Shanghai. This comparison between two types of border effects facilitates a better understanding of the extent of domestic market integration in China. Third, owing to the nature of our data and the new estimation approach we adopt, our estimated border effects are less subject to the measurement error‐related and estimation‐related biases commonly seen in previous studies. We find the estimated border effect between Hong Kong and mainland China to be approximately 266 km, which is substantially larger than that between Guangdong and Shanghai (1.3 km). Both are substantially smaller than the estimated border effects found in many previous studies.